Equality and Discrimination: Lessons from a Research Programme and a Conference - MC GINNITY, FRANCES; RUSSELL, HELEN (ESRI, 2011)
Despite legislation outlawing discrimination across the EU, inequalities between groups appear to be an enduring feature of Irish and European societies. The extent to which inequality is due to discrimination is a matter of continuing debate and controversy. Accurately measuring discrimination is therefore a crucial yet challenging task. This has been a central focus of a research programme on equality and discrimination carried out by the Economic and Social Research Institute and the Equality Authority since 2006, and was the theme of the conference `Making Equality Count? held in Dublin in June 2010. Drawing on economics, sociology and social psychology, the book from the conference, Making Equality Count, highlights advances that have been made in the measurement of discrimination, as well as the range of evidence that has been accumulated on this topic in recent decades. Here we give a flavour of the measurement issues and the salient findings from the book
PUBLISHED
Keywords: Social Policy; Equality and Discrimination